EFFECT OF ERGONOMIC GYMNASTIC ON BLOOD PRESSURE AND LIPID PROFILE HYPERTENSION PATIENT AT SUMBER AGUNG VILLAGE, JATIREJO DISTRICT, MOJOKERTO CITY, INDONESIA - eka nur soemah; agus hariyanto; amar akbar (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Background : Hypertension is the most common disease found in the community. It does not only degrade the quality of life, but it can be life-threatening. Hypertension is known as heterogeneous group of disease because it can affect anyone from different age groups and various economic classes. There are two therapies for hypertension ie pharmacology and nonpharmacology. One of non-pharmacology therapy is doing ergonomic gymnastics. The purpose of this study is to see the effect of ergonomic gymnastics on blood pressure in people with hypertension in Sumber Agung Village, Jatirejo Sub-district, Mojokerto Regency. Method : This research method used one group pre test - post test design with control group. Sampling technique used was simple random sampling, from 80-person population of hypertension patient in Sumber Agung Village Jatirejo Sub-district Mojokerto Regency and become sample number 20 respondents in treatment group, and 20 respondents in control group according to criteria. Data collection using interval scale blood presure and total cholesterol. Analysis using statistical test Paired T test and Independent T-test SPSS 17. Result : From the analysis we got result p value 0,00 <0,05 it indacted that means of blood presure and lipid profile before ergonomic gymnastic and after ergonomic gymnastic shown significat value, it means that ergonomic gymnastic was very effective for blood pressure and lipid profile (total cholesterol). Discussion : Ergonomic gymnastics is one of effective therapy, easy to do and useful. Because ergonomic gymnastics can make the body become relaxed and blood vessels become vasodilated so that the blood flow and oxygen supply becomes smooth and it get impact in lipid profile . keywords : Aergonomic Gymnastic, Blood Pressure, Lipid Profile, Hipertension.